Lessons for major system change: centralization of stroke services in two metropolitan areas of England. (July 2016) - Turner, Simon; Ramsay, Angus; Perry, Catherine; Boaden, Ruth; McKevitt, Christopher; Morris, Stephen; Pursani, Nanik; Rudd, Anthony; Tyrrell, Pippa; Wolfe, Charles; Fulop, Naomi
Objectives: Our aim was to identify the factors influencing the selection of a model of acute stroke service centralization to create fewer high-volume specialist units in two metropolitan areas of England (London and Greater Manchester). It considers the reasons why services were more fully centralized in London than in Greater Manchester. Methods: In both areas, we analysed 316 documents and conducted 45 interviews with people leading transformation, service user organizations, providers and commissioners. Inductive and deductive analyses were used to compare the processes underpinning change in each area, with reference to propositions for achieving major system change taken from a realist review of the existing literature (the Best framework), which we critique and develop further. Results: In London, system leadership was used to overcome resistance to centralization and align stakeholders to implement a centralized service model. In Greater Manchester, programme leaders relied on achieving change by consensus and, lacking decision-making authority over providers, accommodated rather than challenged resistance by implementing a less radical transformation of services. Conclusions: A combination of system (top-down) and distributed (bottom-up) leadership is important in enabling change. System leadership provides the political authority required to coordinate stakeholders and to capitalize on clinical leadership by aligning it with transformation goals. Policy makers should examine how the structures of system authority, with performance management and financial levers, can be employed to coordinate transformation by aligning the disparate interests of providers and commissioners.